Disintegration of the Top Stent on Zenith Abdominal Aortic Stent-Grafts. (April 2016) - Lindström, David; Wahlgren, Carl Magnus; Sonesson, Björn; Resch, Timothy
Purpose: To describe a heretofore unreported complication involving the Zenith Low Profile (LP) stent-graft.Case Report: Two men, aged 75 and 67 years, respectively, underwent abdominal aortic aneurysm repair with a Zenith LP device. At 4 and 3 years, respectively, computed tomography angiography revealed separation of the proximal fixation stent from the stent-graft. In the first patient, there was stent-graft migration but no evidence of an endoleak; however, the aneurysm had grown. A fenestrated cuff was placed, sealing distally in the previous LP graft. The second patient had a type I endoleak. Open surgery was performed, and the main body of the graft was explanted. Postoperative examination of the device revealed that the fixation sutures on the suprarenal stent were still attached to the stent and had eroded through the graft material.Conclusion: Physicians should be aware of the potential for top stent separation from the Zenith LP stent-graft as a cause of endoleak and migration.